Job burnout among employees in food and beverage industry in Klang Valley - Che Azimi, Amin Mustaqim; Saad, Mazni (2020)
The aim of this research is to assess an individual’s experience of burnout in the food and beverage industry in Klang Valley. It is undeniable that the hospitality industry is one of the stressful industry by taking into consideration the nature of work that require employees to be present at all times entertaining customers and fulfilling all their needs. High degree of mental, physical and psychological pressure is among the most common conditions in food and beverage industry that may result in occupational burnout. Therefore, based on LR, this research will study the correlation between variables such as excessive workload, long working hours and role conflict with job burnout in food and beverage industry. A structured questionnaire was developed and administered to the employees using non-probability sampling method. 69 targeted respondents have been identified as the sample for the research. These targeted individuals currently holding either full-time or part-time employment and vary between operational and managerial level. It was found that 100 percent of employees in food and beverage industry in Klang Valley experienced high levels of burnout in the dimensions of depersonalization, 90.9 percent score in the dimension of personal accomplishment meanwhile only 13.6 percent score in the dimensions of emotional exhaustion. The findings from this research may contribute to others, especially higher up management to prepare intervention programs that aim to reduce the employee’s experience on burnout. As the current research approach manages to reveal some valuable insights, it is more remarkable if the research enhances with qualitative approach to the use of semi-structured interviews in determining the causes and effect of the phenomenon. Further follow-up study should be conducted in order to identify thorough state of burnout compared to the current findings. Food and beverage industry, workload, working hours, role conflict, burnout